A Survey on Physical Activity and Non- Communicable Disease Risk Factors Among Physicians in Tertiary Care Hospitals, Mangalore - Gandhi, Hiral; Vaishali K; V Prem; Vijayakumar, K; Adikari, Prabha; B UnniKrishnan (National Journal of Community Medicine, 2012)
Background and objectives: Almost half of the adult disease burden in South Asia is attributable to non-communicable diseases. Earlier literature is limited to evaluating non-communicable disease (NCD) risk factor but, there is a limited literature evaluating physical activity (PA), a modifiable risk factor for NCD among physicians in India. We aimed to assess the NCD risk factors and physical activity using questionnaire among physicians. Methods: 100 physicians with minimum of 5 years of clinical experience, volunteered were included in the present study. NCD risk factors and physical activity were evaluated through WHO STEPS instrument and self-report PA questionnaires. They were administered through face to face interviews. Prevalence of NCD risk factors and level of PA were analyzed. Results: Age group was 37.86±8.85 years. Males and females were 52% and 48%. Alcohol and tobacco use was found in 6% and 1% subjects. HTN and DM were found in 2% population. 69% physicians were found to be in overweight category. Total cholesterol and triglyceride levels were high in 3% and 9% physicians. PA mean score was 1227.2±76 MET min/wk. 20% physicians were found to have low PA level. Conclusion: This study provides first data on PA, a potential modifiable risk factor for non- communicable disease risk factors among physicians in India. Sitting time was found ‘often’ in them. 20% of physicians had a low level of PA and were at high risk for cardio-vascular diseases.